Low-cost ANS encoder for lossless data compression in FPGAs - Pastuła, Magdalena; Russek, Paweł; Wiatr, Kazimierz (International Journal of Electronics and Telecommunications, 2024)
We present the implementation of the hardware ANS compressor in FPGAs. The main goal of the design was to propose a solution suitable to low-cost, low-energy embedded systems. We propose the streaming-rANS algorithm of the ANS family as a target for the implementation. Also, we propose a set of algorithm parameters that substantially reduce the use of FPGA resources, and we examine what is the influence of the chosen parameters on compression performance. Further, we compare our design to the lossless codecs found in literature, and to the streaming-rANS codecs with arbitrary parameters.